2020
DOI: 10.1177/2333794x20976240
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Vitamin D3 in Vitamin D Deficient Adolescents: A Pilot Study

Abstract: Multiple epidemiological studies have shown that vitamin D deficiency is highly prevalent amongst adolescents in the USA. However, recommendations regarding the treatment of vitamin D deficiency in healthy adolescents are not well defined. We carried out a prospective pilot study, to determine whether treatment with 2000 international units of vitamin D3 daily for 3 months, would normalize the vitamin D levels in vitamin D deficient adolescents. Following treatment there was a 56.02% increase in the vitamin D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…This finding is inconsistent with the study by Ponda et al, which demonstrated that an increase in vitamin D levels leads to an increase in HDL 23 . In the study by Kumaratne et al, high vitamin D levels were associated with a decrease in LDL, which is in line with the present study 19 . Additionally, the study by Asmi et al showed that LDL levels were lower in individuals without vitamin D deficiency compared to those with vitamin D deficiency 21 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is inconsistent with the study by Ponda et al, which demonstrated that an increase in vitamin D levels leads to an increase in HDL 23 . In the study by Kumaratne et al, high vitamin D levels were associated with a decrease in LDL, which is in line with the present study 19 . Additionally, the study by Asmi et al showed that LDL levels were lower in individuals without vitamin D deficiency compared to those with vitamin D deficiency 21 .…”
Section: Discussionsupporting
confidence: 93%
“…In the study by Faridi et al, it was also demonstrated that 15% of individuals had vitamin D deficiency, which was relevant to the current study 18 . Furthermore, in the study by Kumaratne et al, vitamin D levels were estimated to be below normal in 20% of individuals 19 . In the study conducted by Khoo et al, the vitamin D level was estimated to be below 20 ng/mL in 17% of individuals, which was within the scope of the present study 19 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation